Augmented Reality Objek Wisata Bogor Menggunakan Algoritma Lucas Kanade Dengan Metode Marker Based Tracking - Fikry Ali Sya’ Dani; M Iwan Wahyuddin; Winarsih Winarsih (STMIK Budi Darma, 2021)
Information technology today, is very developed and easy to find. Especially in information on Bogor tourist attractions such as the Bogor Palace, Tugu Kujang, and Pakansari Stadium. However, the data information held is not completely valid. Because many tourists get data that is not suitable, due to the lack of information obtained. Therefore, the researchers tried to make an android-based